Benefits of Halal Meat Consumption as Nutrition for Tuberculosis Prevention - Kartini, Puri Ratna; Ningtiyas, Erika Rahayu; Vevi Maritha (Universitas Sahid Surakarta, 2023)
One of the non-pharmacological treatments in tuberculosis patients is the fulfillment of good nutrition. Complete nutrition in meat is able to keep the body healthier, thus preventing the outbreak of tuberculosis. Meat used to fulfill nutritional needs in an effort to prevent tuberculosis needs to be considered halal. Knowledge about halal meat as nutrition to prevent tuberculosis needs to be given to the community, both those who have been exposed and those who have not. Garon Village, Kawedanan Subdistrict, Magetan Regency is an area where the community has not been exposed to tuberculosis, but the area is cold in the Bancak mountainous area so the potential for people to contract tuberculosis is very high. Therefore, counseling is needed to increase community knowledge about the importance of halal meat consumption as an effort to fulfill nutrition to prevent tuberculosis. The result of this counseling was an increase in knowledge about the benefits of halal meat consumption to prevent tuberculosis by 85.3%. This value can be a reference that this service activity has an impact on the community.